2006
DOI: 10.1002/hec.1125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EQ-5D and SF-6D utilities in mental health patients

Abstract: SummaryVarious preference-based measures of health are available for use as an outcome measure in cost-utility analysis. The aim of this study is to compare two such measures EQ-5D and SF-6D in mental health patients.Baseline data from a Dutch multi-centre randomised trial of 616 patients with mood and/or anxiety disorders were used. Mean and median EQ-5D and SF-6D utilities were compared, both in the total sample and between severity subgroups based on quartiles of SCL-90 scores. Utilities were expected to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
114
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 19 publications
(27 reference statements)
8
114
0
1
Order By: Relevance
“…50 Recent years have seen the development of preference-based condition-specific measures, 51 including one for common mental health problems. 52 However, the pressure to use generic measures remains and has started to impact on the scales used in clinical studies and, most recently in the UK, in routine patient-reported outcome measurement.…”
Section: The Appropriateness Of the Eq-5d And Sf-36 In Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…50 Recent years have seen the development of preference-based condition-specific measures, 51 including one for common mental health problems. 52 However, the pressure to use generic measures remains and has started to impact on the scales used in clinical studies and, most recently in the UK, in routine patient-reported outcome measurement.…”
Section: The Appropriateness Of the Eq-5d And Sf-36 In Mental Healthmentioning
confidence: 99%
“…In all, there were 22 studies 50, identified with data on the validity and/or responsiveness of the generic HRQoL measures in depression and anxiety for EQ-5D and SF-6D. Fourteen studies 50,129,[136][137][138][139][142][143][144][145][146][147][148][149] had data on the EQ-5D and seven 130,131,[133][134][135]140,141 contained data on the SF-6D. Studies were undertaken in at least 12 countries (a number covered Europe).…”
Section: Depression and Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…However, although these instruments all have these characteristics, many researchers have detected discrepancies in the utility values obtained by different instruments, mainly due to differences of the descriptive part of the measure. Indeed, an analysis of some of the studies published in recent years in the area of health economics and the measurement of HRQoL, [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] including studies with a wide diversity of populations and interventions, shows only a weak or moderate level of agreement between different preferencebased instruments.…”
mentioning
confidence: 99%
“…Several studies have been published with comparisons between these two instruments. 33,49,50 However, most studies have been aimed at comparing and analysing the performance of the instruments in the context of a specific disease, 36,38,[40][41][42][43][44]46,48,[51][52][53][54][55][56][57] or among specific groups of people. 32,37,39 Few studies have been devoted to the comparison of the EQ-5D and the SF-6D in the general population, 45,58 along with the comparison of their performances for more than one disease.…”
mentioning
confidence: 99%